A Fifth Metatarsal Fracture or a Rare Anatomical Variant?: A Report of Two Cases of Symptomatic Os Vesalianum Pedis and a Review of the Literature - Petrova, Kristina; Rangelov, Svetlomir; Gaydarski, Lyubomir; Landzhov, Boycho; Georgiev, Georgi P. (Acta medica Lituanica, 2025)
Background: Accessory bones of the foot are common anatomical variants, with Os Vesalianum Pedis (OVP) representing a rare example located near the base of the fifth metatarsal within the peroneus brevis tendon. Although typically asymptomatic, OVP can become painful following trauma and may be misdiagnosed as a fracture, leading to inappropriate management.Case presentation: We present two cases of symptomatic OVP in patients who reported lateral foot pain after acute ankle inversion injuries. Following radiological evaluation at a regional polyclinic, both patients were initially diagnosed with fractures of the fifth metatarsal base and referred to a traumatologist. However, further physical examination and detailed review of previous radiographs, revealing well-corticated, smoothly contoured ossicles, led to the correct diagnosis of OVP. Both patients were treated conservatively with rest, ice, elevation, physiotherapy, and NSAIDs, achieving complete functional recovery within three weeks.Conclusions: These cases highlight the importance of recognizing OVP as a potential cause of lateral foot pain after trauma. Accurate diagnosis based on imaging characteristics can prevent mismanagement. Conservative treatment remains highly effective, and awareness of OVP is essential for appropriate clinical decision-making.